The Duty to Accommodate Disabled Employees - Taras, Daphne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
Drawing on recent legal decisions involving disabled workers, this paper assesses the trends and implications regarding duty to accommodate. In the first section, four specific issues are developed to illustrate the evolution of human rights principles as they are interpreted through tribunals and arbitrations. The second section applies the issues to a specific group of people, diabetic shiftworkers. The focus on diabetic shiftworkers offers a vivid example of adverse effect discrimination, and demonstrates the impact of human rights decisions.